A socio-legal analysis of development vs. ecological justice: A case study of indigenous peoples' human rights violations in the food estate national strategic project in Gunung Mas - Violenza Alif (PT WIM Solusi Prima, 2026)
The Food Estate National Strategic Project (NSP) in Gunung Mas Regency, Central Kalimantan, was conceived as a solution to the threat of a global food crisis. However, its implementation has triggered a severe clash between the state’s development ambitions and the ecological rights of the Dayak Indigenous Peoples. This journal analyzes how the Food Estate project instigates human rights violations against indigenous communities, examined through the lens of Ecological Justice. The research employs a qualitative normative-legal method with a socio-legal approach, utilizing secondary data analysis (desk research). The findings demonstrate that this project disregards the principle of Free, Prior, and Informed Consent (FPIC), expropriates sociological living spaces, excludes indigenous forest rights following the Constitutional Court Decision No. 35/PUU-X/2012, and causes severe environmental degradation (deforestation and flooding) that burdens local communities in the absence of distributive justice. The state prioritizes corporate food security at the expense of ecological sustainability and indigenous livelihoods.